Avaliação de viabilidade técnico-econômica de sistema CCS em uma termelétrica brasileira a carvão - Gomes, Rachel Tamburini, 1993- (2023)
Orientadores: Arnaldo Cesar da Silva Walter, Carla Kazue Nakao Cavaliero